(untitled) (Update Dental College Journal, 2019)
Background: Pulpotomy is measured as one of the most worldwide accepted favourable clinical procedure for the treatment of deciduous tooth with reversible pulpitis with carious destruction of tooth tissue. Objectives: To evaluate the clinical and radio-graphical findings of primary tooth with reversible pulpitis by Biodentine and Calcium Hydroxide as pulpotomy material. Study Design: Randomized comparative study. Study place and period: Conservative Dentistry & endodontics department of Bangabandhu Sheikh Mujib Medical University, Dhaka, September 2013 to September 2014. Study Population: The study population comprised of patients having primary tooth with reversible pulpitis irrespective of sex. Methods/Procedure: According to inclusion and exclusion criteria, out of 100 primary teeth 50 teeth were treated with Biodentine (Group-A) and the remaining 50 teeth were treated with Ca(OH)2 (Group-B). Clinical and radiographic follow up examination were done at 3months,6 months and 12 months’ interval to evaluate the rate of postoperative pain, swelling and periapical radiolucency. Statistical package for Social Science (SPSS) version 17 was used to analyze the collected data Main outcomes measures (s): 01. Pain 02. Dentinal bridge 03. Root resorption Results: At 3 months observation period, Biodentine and Ca(OH)2 pulptomy of primary teeth showed 100% success rate in treating teeth with reversible pulpitis; neither pain nor swelling or radiographic sign of resorption was observed. At 6 and 12 months following the completion of treatment except in two case in group A and four case in group B in observation period, there results were similar to that of 3 months. Two Biodentine (4%) and four Ca(OH)2 (8%) therapy reported pain, swelling. There was no statistical difference between the two group (p>0.05). Conclusion: So, we can say that clinical and radiographic end result of Biodentine is better than Ca(OH)2 as a pulpotomy material in mature primary tooth with reversible pulpitis. Update Dent. Coll. j: 2019; 9 (1): 37-41